2018
DOI: 10.1364/oe.26.009039
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical dual D-shape photonic crystal fibers for surface plasmon resonance sensing

Abstract: Symmetrical dual D-shape photonic crystal fibers (PCFs) for surface plasmon resonance (SPR) sensing are designed and analyzed by the finite element method (FEM). The performance of the sensor is remarkably enhanced by the directional power coupling between the two fibers. We study the influence of the structural parameters on the performance of the sensor as well as the relationship between the resonance wavelengths and analyze refractive indexes between 1.36 and 1.41. An average spectral sensitivity of 14660 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(92 citation statements)
references
References 36 publications
1
85
0
Order By: Relevance
“…It is observed that the resonance peak shift increases with the increase of analyte RI resulting in high sensitivity for larger RI. Note that the proposed sensor shows similar loss characteristics to previously reported [32] highly sensitive sensors. Moreover, from Fig.…”
Section: Investigation Of Sensor Performance By Optimizing Different supporting
confidence: 77%
See 3 more Smart Citations
“…It is observed that the resonance peak shift increases with the increase of analyte RI resulting in high sensitivity for larger RI. Note that the proposed sensor shows similar loss characteristics to previously reported [32] highly sensitive sensors. Moreover, from Fig.…”
Section: Investigation Of Sensor Performance By Optimizing Different supporting
confidence: 77%
“…According to WI method the wavelength sensitivity can be calculated according to the following Eq. [32],…”
Section: Design and Theoretical Modelling Of The Proposed Pcf-spr Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the design of PCF-SPR biosensors has attracted researcher's attention because of their applications in many areas, such as the analysis of biomolecular interactions (BIA) and precise detection of chemical and biological analytes [8]. For example, a PCF-SPR biosensor for the low refractive index (RI) detection was proposed by Liu et al [9] with low spectral sensitivity and amplitude sensitivity of 6000 nm/RIU and 600 RIU −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%